Pengaruh motivasi kerja dan disiplin kerja terhadap kinerja pegawai Yonif 142/KJ - Candra Candra; Zulfina Adriani; Sry Rosita (Jurnal Dinamika Manajemen, 2021)
This study aims to: 1) To determine and analyze the description of work motivation, work discipline and performance of administrative employees of Yonif 142 / KJ, 2) To determine and analyze the effect of work motivation on the performance of administrative employees of Yonif 142 / KJ, 3) To determine and analyze the effect of work discipline on the performance of the administrative staff of Yonif 142 / KJ, and 4) To know and analyze the motivation and work discipline simultaneously affect the performance of the administrative staff of Yonif 142 / KJ by using multiple linear regression analysis tools. Based on the research results indicate that the work motivation in the results of this study is "high enough" and shows that the respondents are motivated to work because they get a promotion if the job can be done optimally and achieve performance targets. Work discipline in the results of this study is "high" and indicates that the respondents expect very good work discipline such as coming to the office on time. Employee performance in the results of this study is "good" and shows that the quality of employee performance has contributed greatly to the leadership. Motivation and work discipline have a positive and significant effect on employee performance at Yonif 142 / KJ. Based on the simultaneous test, the variables of motivation and work discipline together (simultaneously) have a significant effect on employee performance variables.